(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Landslides occurring at or near dam structures are among the predominant forms of geological hazards responsible for significant loss of life, property damage, and environmental degradation worldwide. To understand the risk, this study evaluates the landslide susceptibility in the nearly ageing Bukit Kwong Dam where ageing denotes to time-related deterioration occurring fifty years of operation using an integrated approach of Unmanned Aerial Vehicles (UAV), Geographic Information System (GIS) and frequency ratio model selected due to its simplicity and ability to provide numerical measure of the relative importance in the landslide occurrence. The proposed methodology involves the preparation of a landslide inventory, generation of multiple thematic maps representing factors influencing slope instability, including aspect, slope, plan curvature, profile curvature, elevation, land use, distance from river, Normalized Difference Vegetation Index (NDVI), rainfall, and distance from road. These thematic layers were subsequently integrated within a GIS environment using the frequency ratio technique to produce a Landslide Susceptibility Map (LSM). The LSM delineated five susceptibility classes, ranging from very low (48%), low (34%), moderate (12%), high (5%), and very high (1%). According to their high frequency values, slope, land use, plan and profile curvatures, and distance from river were identified as the most influential predisposing factors contributing to landslide occurrence. The performance and accuracy were evaluated using Area Under Curve (AUC), yielding a score of 0.85. The outcomes provide useful baseline information to identify landslide-prone areas for dam safety evaluations and slope management strategies in the region.